The Perception and Challenges in Community-Based Ecotourism (CBE) Development: Insight from Kampong Rasuna, Tenghilan, Tuaran Sabah - Muhammad Nur Noordin; Orryel Jaunis; Russel @ Andy Immit Mojiol (Penerbit UTS, 2022)
Ecotourism is often associated with nature and is environmentally friendly. Community-based ecotourism (CBE) is a tourism activity involving communities or residents. The first objective of this research is to study the local community's perception of the development of community-based ecotourism in Kampong Rasuna, Tenghilan. The second objective is to identify the local community's challenges in carrying out ecotourism activities in Tenghilan. This study uses convenience sampling to determine the sample size, and a total of 100 respondents were selected during data collection. For the perception of CBE development, the highest mean score is 4.42, where the majority of the respondents agree that Rasuna is developed to become a tourist centre. The respondents agree that the tourism activities in their village would improve their income, employment, and business opportunities. For the challenges, the highest mean score was recorded for the shortage of capital. The respondents revealed that although the village has clean water and electric facilities, other tourism-related infrastructures are limited, thus becoming a hurdle to further boosting the ecotourism activities in the area.